2015
DOI: 10.1002/eji.201445314
|View full text |Cite
|
Sign up to set email alerts
|

The expression of mouse CLEC‐2 on leucocyte subsets varies according to their anatomical location and inflammatory state

Abstract: Expression of mouse C‐type lectin‐like receptor 2 (CLEC‐2) has been reported on circulating CD11bhigh Gr‐1high myeloid cells and dendritic cells (DCs) under basal conditions, as well as on a variety of leucocyte subsets following inflammatory stimuli or in vitro cell culture. However, previous studies assessing CLEC‐2 expression failed to use CLEC‐2‐deficient mice as negative controls and instead relied heavily on single antibody clones. Here, we generated CLEC‐2‐deficient adult mice using two independent appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 53 publications
2
41
0
Order By: Relevance
“…Neutrophils have been reported to express CLEC-2 in 1 study 34 but not another. 25 The finding that platelet-specific knockout mice have decreased thrombosis suggests a predominant role of CLEC-2 on platelets in DVT initiation. The reason for different median thrombus size in the WT (Cre 2 littermates) groups of BLOOD, 6 APRIL 2017 x VOLUME 129, NUMBER 14 CLEC-2 PROMOTES DVT 2015…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils have been reported to express CLEC-2 in 1 study 34 but not another. 25 The finding that platelet-specific knockout mice have decreased thrombosis suggests a predominant role of CLEC-2 on platelets in DVT initiation. The reason for different median thrombus size in the WT (Cre 2 littermates) groups of BLOOD, 6 APRIL 2017 x VOLUME 129, NUMBER 14 CLEC-2 PROMOTES DVT 2015…”
Section: Discussionmentioning
confidence: 99%
“…The latter study also reported accumulation of Clec-2 on myeloid cells and NK cells upon lipopolysaccharide (LPS) challenge together with a de novo appearance of Clec-2 on B cells (44). A more recent report, however, attributed Clec-2 on mouse B cells to the acquisition from exogenous sources, for example, by trogocytosis, and showed that Clec-2 on mouse myeloid cells is lost during the entrance of these cells into secondary lymphoid organs (45). The function of CLEC-2 on platelets is well defined as stimulating platelet activation and aggregation (10,24,41).…”
Section: Hemitam Receptorsmentioning
confidence: 92%
“…10 Podoplanin is the only described endogenous ligand of the C-type lectin-like receptor 2 (CLEC-2), 11 which is expressed by platelets 12 and activated dendritic cells (DCs). [13][14][15] CLEC-2 signaling is involved in platelet activation, 12 DC motility 15 and in the maintenance of vascular integrity, 16 LN structure and development. 17 Podoplanin global knockout mice die shortly after birth because of a failure to inflate their lungs.…”
mentioning
confidence: 99%